High sensitivity colorimetric determination of L-cysteine using gold nanoparticles functionalized graphene oxide prepared by photochemical reduction method - Dizman, H. Mirac; Kazancioglu, Elif Ozcelik; Shigemune, Takuya; Takahara, Shigeru; Arsu, Nergis (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
This study aimed for the development of a cost effective and efficient method for L-cysteine detection, without employing expensive instrumentation within a short analysis time. The proposed method has been involved in the photochemical preparation of gold nanoparticles and gold nanoparticles on graphene oxide nanostructures. The gold nanoparticles and gold nanoparticles on graphene oxide acted as simple and sensitive nano-sensors for L-cysteine, due to the molecular structure of the L-cysteine presented -NH2 and -SH, which is very attractive for coordination to gold nanoparticles and crosslink gold nanoparticles causing aggregation and color change. By using the gold nanoparticles on graphene oxide as a probe, the colorimetric detection of L-cysteine in a nanomolar order concentration was demonstrated. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Gold nanoparticle; L-cysteine; Graphene oxide; Colorimetric detection; Benzophenone; TURKEVICH METHOD; PHOTOINITIATOR; SENSOR; AGGREGATION; ACID; Spectroscopy